WGCNA analysis revealing molecular mechanism that bio-organic fertilizer improves pear fruit quality by increasing sucrose accumulation and reducing citric acid metabolism - Wang, Zhonghua; Yang, Han; Ma, Yanwei; Jiang, Gaofei; Mei, Xinlan; Li, Xiaogang; Yang, Qingsong; Kan, Jialiang; Xu, Yangchun; Yang, Tianjie; Lin, Jing; Dong, Caixia (Frontiers in Plant Science, 2022)
It’s been long known that the application of organic fertilizer (OF) and bio-organic fertilizer (BF) which containing beneficial microorganisms to pear trees can both significantly improve fruit quality and yield. In order to reveal the mechanism of BF and OF regulating fruit growth and quality in pear, the effects of BF and OF on the photosynthetic characteristics and the accumulation of major sugars and organic acids of the pear fruit were quantified compared with chemical fertilizer (CF). Additionally, the molecular mechanisms regulating pear fruit development and quality were studied through transcriptome analysis. The three treatments were conducted based on the same amounts of nitrogen supply. The results showed that compared with CF, BF and OF treatments increased the fruit yield, and also significantly improved the photosynthesis efficiency in pear. BF and OF both significantly increased the sucrose content but significantly decreased the fructose and glucose content within the pear fruit. The amount of malic acid was significantly higher in OF treatment. Compared with CF and OF, BF significantly increased the sugar-acid ratio and thus improved the fruit quality. Transcriptome analysis and WGCNA revealed that the sugar metabolism of fruits applied with the BF was enhanced compared with those applied with CF or OF. More specifically, the expression of SDH was higher in BF, which converts sorbitol into fructose. For both of the OF and BF, the transcript abundance of sugar transporter genes was significantly increased, such as SOT, SUT14, UDP-GLUT4, UDP-SUT, SUC4, SUT7, SWEET10 and SWEET15 which ensures sugar transportation. The genes involved in organic acid metabolism showed decreased transcripts abundance in both BF and OF treatments, such as VAP and cyACO, which reduce the conversion from succinate to citric acid, and decrease the conversion from citric acid to malic acid in the TCA cycle through Pept6. In conclusion, the application of BF and OF improved fruit quality by regulating the expression of sugar and organic acid metabolism-related genes and thus altering the sugar acid metabolism. Both BF and OF promote sucrose accumulation and citric acid degradation in fruits, which may be an important reason for improving pear fruit quality.